Adaptation to Spanish of the “Relational Needs Satisfaction Scale”: Translation and psychometric testing - Iraurgi, Ioseba; Gómez-Marroquín, Ignacio; Erskine, Richard; Mauriz, Amaia; Martínez-Rodríguez, Silvia; Gorbeña, Susana; Žvelc, Gregor (Frontiers in Psychology, 2022)
This article aims to adapt to Spanish the Relational Needs Satisfaction Scale (RNSS) and to test the factor structure with a clinical and a non-clinical sample. A total of 459 individuals completed the RNSS, a measure of life satisfaction and of psychological wellbeing. Results showed that the translation was adequate. An exploratory and confirmatory factor analysis was conducted followed by the test of three models that confirmed the five-factor structure and the second-order global factor proposed in the original study, and in adaptations to other languages. The advantages and disadvantages of these models are discussed. Correlations of the RNSS with life satisfaction and psychological wellbeing measures were in the expected direction, providing evidence of convergent validity. The Spanish version of the RNSS is a valid and reliable measure of the construct it was intended to measure, though some improvements in item wording could be incorporated and tested (for instance, item 18 should be positively worded as the rest of the items in order to avoid the effect of negative wording).